Consumer Credit Administration Process at Bank Sumsel Babel KCU Arivai Palembang - M. Sholeh Awaludin; Saprida Saprida; Havis Aravik; Ahmad Tohir (Penerbit dan Percetakan CV. Picmotiv, 2026)
The consumer credit administration process is a crucial step in the distribution of banking financing because it determines the smoothness, accuracy, and security of the credit disbursement process to customers. Frequently encountered problems include incomplete documents, inconsistent administrative data, miscommunication between work units, and the accumulation of archives that can potentially hinder the credit verification and approval process. This report aims to describe the consumer credit administration process at Bank Sumsel Babel KCU Arivai Palembang, explain the role of student interns in supporting administrative activities, and identify obstacles and their resolutions. The method used is a qualitative descriptive approach with data collection techniques such as observation, interviews, documentation, and literature studies. The results of the study indicate that the consumer credit administration process is carried out through the stages of credit application, document and SLIK inspection, legality check, feasibility evaluation, and credit agreement. Student interns play a role in assisting with data input, document verification, archiving, and contract administration preparation, thus supporting the smooth operation of the work unit. Obstacles encountered include incomplete customer documents, errors in form filling, suboptimal coordination, and limited archive space. Improvement efforts were made through the implementation of document checklists, enhanced internal communication, customer education, and systematic archive management, thereby enhancing administrative effectiveness and the quality of consumer credit services.